Description of JA Medical Skincare Medan Beauticianâ€™s Low Back Pain Based on Duration of Work - Vivienne; Arsyad, Abdurrahman Mousa; Lubis, Bastian; Lubis, Hilfan Ade Putra (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2024)
Introduction: Low Back Pain (LBP) is defined as pain and discomfort located below the costal margin to the inferior gluteal fold, with or without pain in the legs. LBP is a common condition that can occur in all age groups with acute or chronic episodes. Beauticians are more susceptible to musculoskeletal disorders. This line of work tends to involve limited positions, repetitive movements, standing for more than 8 hours or sitting in a bent position during activities. This study aims to determine the characteristics of low back pain based on work duration among beauticians of the JA Medical Skincare beauty clinic Medan. Method: The method used in this research was descriptive quantitative with a total sampling technique. The research population was 60 beauticians from the JA Medical SkincareÂ Beauty Clinic Medan. The data were collected by having the respondents fill out a questionnaire. Results: The research results revealed that beauticians at the JA Medical Skincare beauty clinic who were at risk of experiencing low back pain were individuals aged under 30 years (51.8%), those with BMI > 27 or categorized as obese (60%), and those with a working duration of more than 8 hours (49,1%). These groups exhibited higher percentages of complaints related to low back pain. In general, almost all ages have the potential to experience low back pain. Beauticians who work long hours and do not pay attention to ergonomic factors would have caused continuous static loads on their back and are at risk of experiencing complaints of low back pain. Keywords: Beautician; Duration of work; Low back pain